container
The container addresses the challenges of adhesion and heat resistance in PET resin-based containers by using a copolymerized polyethylene terephthalate resin with a specific isophthalic acid ratio and melting point range, resulting in high adhesion and heat-resistant composite substrates.
Patent Information
- Application Number
- JP2021542953
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-08-26
- Filing Date
- 2020-08-26
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2040-08-26
AI Technical Summary
Existing containers made from composite substrates with PET resins face challenges in achieving high adhesion between the paper substrate and the resin layer while maintaining sufficient heat resistance, especially under high-temperature conditions such as baking or microwave heating.
A container is designed using a composite substrate with a paper substrate layer and a copolymerized polyethylene terephthalate resin layer, where the copolymerization ratio of isophthalic acid is between 1 mol% and less than 10 mol%, and the resin has a melting point of 235°C to 250°C, ensuring high adhesion and heat resistance.
The container achieves high adhesion between the substrate and resin layers, preventing defective molding and ensuring stability under high-temperature conditions, while also offering improved heat resistance and reduced fossil resource usage.
Smart Images

Figure 0007671690000002 
Figure 0007671690000003 
Figure 0007671690000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a container, and more particularly to a container used as a paper cup or case for storing beverages, food, etc. [Background technology]
[0002] 2. Description of the Related Art Conventionally, there have been containers for storing beverages, foods, and the like, which use a composite substrate in which a synthetic resin is laminated on one or both sides of a paper substrate.
[0003] Japanese Patent No. 4750909 discloses a container using homopolyethylene terephthalate (PET) as the resin.
[0004] Furthermore, Japanese Patent No. 5680917 discloses a container using a copolymerized PET resin (copolymerization component ratio is 10 mol % to 40 mol %) as the resin. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent No. 4750909 [Patent Document 2] Japanese Patent No. 5680917
[0006] Homo PET as used in Japanese Patent No. 4750909 generally has a relatively high melting point of about 255°C, and in order to form a uniform film on the surface of the paper substrate by extrusion lamination, the extrusion temperature of the resin must be as high as more than 310°C. However, PET resin is prone to hydrolysis under high temperature conditions. Therefore, it is often assumed that homo PET resin, which has a high melting point, will have higher heat resistance, but if the extrusion temperature is too high, hydrolysis will occur in part of the PET resin on the surface of the container formed after extrusion lamination, resulting in a decrease in the heat resistance of that part and the entire container. On the other hand, if the extrusion temperature is lowered to reduce the effect of hydrolysis, the heat resistance will increase, but the melt viscosity during extrusion lamination will increase, making it difficult to form a uniform film on the paper surface. Even if the film is successfully formed, the high melt viscosity of the resin will result in poor adhesion to the paper during extrusion onto the paper surface, and when a container is formed using such a composite substrate, poor molding of the container due to decreased adhesion and delamination between the paper and the PET resin will easily occur.
[0007] In addition, the copolymerized PET resin of Japanese Patent No. 5680917 has a relatively low melting point of 230°C or less, so that the extrusion temperature of the resin can be kept low, hydrolysis under high temperature conditions is unlikely to occur, and the decrease in adhesion to the paper during extrusion onto the paper surface can be reduced. However, since the melting point is low at 230°C or less, the heat resistance of the container after molding is poor. In particular, when filling a container with food that requires cooking, such as gratin, for example, a baking process under high temperature conditions is required to brown the surface after filling the container, and high heat resistance is required because the temperature becomes high locally. In addition, when the container is distributed to the market as a food product after the baking process and packaging, and when general consumers heat it in a microwave oven and eat it, the container becomes hot, so high heat resistance is also required. However, the container of Japanese Patent No. 5680917, which has poor heat resistance, could not fully meet such requirements.
[0008] The present invention has been made to solve the above-mentioned problems, and has an object to provide a container which has high adhesion between a substrate layer and a resin layer and which has high heat resistance. DISCLOSURE OF THEINVENTION
[0009] In order to achieve the above object, a container in a first aspect of the present invention is a container composed of a composite substrate having a base layer made of paper and a resin layer made of copolymerized polyethylene terephthalate resin laminated on at least one side of the base layer, wherein the copolymerized polyethylene terephthalate resin is a copolymerized polyethylene terephthalate resin obtained by copolymerization with isophthalic acid, and the copolymerization ratio of isophthalic acid in the copolymerized polyethylene terephthalate resin is 1 mol % or more and less than 10 mol %.
[0010] With this configuration, the container has high adhesion between the base layer and the resin layer and also has high heat resistance.
[0011] In a second aspect of the present invention, in the container according to the first aspect of the invention, the copolymerized polyethylene terephthalate resin has a melting point of 235°C or higher and 250°C or lower.
[0012] By configuring in this way, the melting point falls within a suitable numerical range.
[0013] A container in a third aspect of the present invention has the configuration of the first or second aspect of the invention, wherein the adhesion of the resin layer to the base layer is 4N / 50mm or more.
[0014] Such a configuration provides favorable adhesion.
[0015] A container in a fourth aspect of the present invention has the configuration of any one of the first to third aspects of the invention, wherein the copolymerization ratio of isophthalic acid in the copolymerized polyethylene terephthalate resin is 1.5 mol % or more and 2.2 mol % or less.
[0016] With this configuration, the adhesion between the base layer and the resin layer and the heat resistance of the container become more favorable.
[0017] A container in a fifth aspect of the present invention has a configuration according to any one of the first to fourth aspects, wherein the copolymerized polyethylene terephthalate resin is a biomass polyethylene terephthalate resin derived from living organisms and has a bio-based carbon content of 5% or more.
[0018] Such a configuration can reduce the amount of fossil resources used and improve carbon neutrality.
[0019] A container in a sixth aspect of the present invention has a configuration according to any one of the first to fifth aspects of the invention, and comprises a bottom and a side wall rising from a peripheral edge of the bottom, the bottom and the side wall being connected by thermal bonding.
[0020] With this configuration, the bottom and the sidewall are firmly attached to each other.
[0021] A container in a seventh aspect of the present invention is formed by press molding or folding molding of a single sheet of base paper obtained from the composite substrate in the configuration of any one of the first to fifth aspects of the invention.
[0022] With this configuration, the container becomes a press-molded product or a molded product by bending.
[0023] As described above, the container in the first aspect of the present invention has high adhesion between the base material layer and the resin layer and is highly heat resistant, which prevents defective molding of the container and makes it suitable for use when the contents become hot or undergo a baking process.
[0024] In the container according to the second aspect of the present invention, in addition to the effects of the invention according to the first aspect, the melting point falls within a suitable numerical range, so that the adhesion between the base layer and the resin layer and the heat resistance of the container are suitable.
[0025] In addition to the effects of the first or second aspects of the invention, the container according to the third aspect of the present invention has good adhesion, and therefore molding defects of the container can be effectively prevented.
[0026] The container in the fourth aspect of the present invention has the same effects as any of the first to third aspects, and in addition, the adhesion between the base layer and the resin layer and the heat resistance of the container are more suitable, making it more convenient to use.
[0027] In addition to the effects of any of the first to fourth aspects of the invention, the container in the fifth aspect of the present invention can reduce the amount of fossil fuel-derived materials used and improve carbon neutrality, thereby improving sustainability and contributing to environmental conservation.
[0028] A container in a sixth aspect of the present invention has the effect of any one of the first to fifth aspects, and in addition, the bottom and the side wall are firmly bonded to each other, resulting in a stably molded container.
[0029] A container in a seventh aspect of the present invention has the effect of any one of the first to fifth aspects, and in addition, since the container is a press-molded product or a molded product by folding, the container is stably molded. [Brief description of the drawings]
[0030] [Figure 1] 1 is a cross-sectional view showing the overall structure of a container according to a first embodiment of the present invention. [Diagram 2] FIG. 2 is an enlarged cross-sectional view of the “X” portion shown in FIG. [Diagram 3] FIG. 4 is a cross-sectional view showing the overall structure of a container according to a second embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0031] FIG. 1 is a cross-sectional view showing the overall structure of a container according to a first embodiment of the present invention, and FIG. 2 is an enlarged cross-sectional view of a portion "X" shown in FIG.
[0032] With reference to these figures, a container 1 is mainly composed of a bottom portion 2 and a side wall portion 3 rising from the peripheral edge of the bottom portion 2.
[0033] Referring to Figure 2, the side wall portion 3 is composed of a composite substrate 7 having a substrate layer 10 made of paper and a resin layer 11 made of copolymerized polyethylene terephthalate resin laminated on the inner surface of the substrate layer 10 (the surface in the direction in which the contents are stored).
[0034] The bottom 2 is also made of a composite substrate 7 having the same structure as the side wall 3, and the bottom 2 and the side wall 3 are connected by thermal bonding. Specifically, a side wall member (unfolded shape of the side wall 3) and a bottom member (unfolded shape of the bottom 2) of a predetermined shape are punched out from the composite substrate 7, and then the ends of both members are bonded together by a known method such as thermal bonding to form the container shape.
[0035] The copolymerized polyethylene terephthalate resin in the present invention is a copolymerized polyethylene terephthalate resin obtained by copolymerization with isophthalic acid (IPA), and the copolymerization ratio of isophthalic acid in the copolymerized polyethylene terephthalate resin is 1 mol % or more and less than 10 mol %.
[0036] By configuring it in this manner, the container has high adhesion between the base material layer 10 and the resin layer 11 and is highly heat resistant, thereby preventing molding defects in the container 1 and making it suitable for use when the contents become hot or undergo a baking process.
[0037] The copolymerization ratio of isophthalic acid is preferably 1.5 mol% or more and 8 mol% or less, and more preferably 1.5 mol% or more and 2.2 mol% or less. In this way, the effects of improving adhesion and improving heat resistance are more suitably achieved. Generally, polyethylene terephthalate resin is obtained by polycondensation of an acid component mainly composed of terephthalic acid and a glycol component mainly composed of ethylene glycol, but the copolymerized polyethylene terephthalate resin used in the present invention contains isophthalic acid in addition to terephthalic acid as an acid component, and the copolymerized polyethylene terephthalate resin is obtained by copolymerizing this isophthalic acid at a predetermined ratio. In addition, other acid components may be contained within a range that does not impair the effects of the present invention, and the glycol component may contain components such as diethylene glycol in addition to ethylene glycol. In addition, the copolymerized polyethylene terephthalate resin used in the present invention may be a mixture of polyethylene terephthalate resins having different copolymerization ratios and adjusted to a predetermined copolymerization ratio suitable for the present invention. For example, a homopolyethylene terephthalate resin and a copolymerized polyethylene terephthalate resin may be mixed in a predetermined ratio to adjust the copolymerization ratio to a predetermined ratio suitable for the present invention, or polyethylene terephthalate resins having different copolymerization ratios may be mixed in a predetermined ratio to adjust the copolymerization ratio to a predetermined ratio suitable for the present invention. 1 It can be calculated by subjecting it to qualitative and quantitative analysis by H-NMR spectroscopy. 1 The monomer units composed of terephthalic acid and the monomer units composed of isophthalic acid in the copolymerized polyethylene terephthalate resin are estimated from the spectrum obtained by H-NMR spectrum measurement, and the composition ratio (molar ratio) of each monomer unit in the copolymerized polyethylene terephthalate resin is calculated from the peak area ratio of the spectrum, and the ratio (%) of the "isophthalic acid monomer unit molar ratio" to the "total of the terephthalic acid monomer unit molar ratio and the isophthalic acid monomer unit molar ratio" can be calculated.
[0038] Furthermore, the copolymerized polyethylene terephthalate resin in the present invention preferably has a melting point of 235° C. or more and 250° C. or less. With this configuration, the melting point falls within a suitable range, and the extrusion temperature during extrusion lamination can be kept relatively low while the melting point itself is sufficiently high, resulting in suitable adhesion between the base layer 10 and the resin layer 11 and suitable heat resistance of the container 1. The melting point can be measured by differential scanning calorimetry (DSC).
[0039] Furthermore, the adhesion of the resin layer 11 to the base layer 10 in the present invention is preferably 4N / 50mm or more. With this configuration, the adhesion is favorable, and molding defects of the container 1 can be favorably prevented. From the viewpoint of molding defects, the higher the adhesion value, the better, so there is no particular upper limit value for the adhesion, but considering the ease of disassembling and dismantling the container to reduce the volume of waste after use as a container, it is sufficient if the adhesion is about 20N / 50mm or less. The adhesion can be measured by the measurement method in the examples described later.
[0040] Furthermore, the polyethylene terephthalate resin in the present invention is preferably a biomass polyethylene terephthalate resin derived from a living organism (derived from a biomass resource) with a bio-based carbon content of 5% or more. The polyethylene terephthalate resin is a resin obtained by polycondensation of ethylene glycol and terephthalic acid as the main components, and most of the polyethylene terephthalate resin (including those in the above-mentioned Japanese Patent Nos. 4750909 and 5680917) is derived from a fossil resource. By making it into a biomass polyethylene terephthalate resin obtained from a living organism such as sugar cane, the amount of fossil resources used can be reduced and carbon neutrality is improved, which improves sustainability and contributes to environmental conservation.
[0041] In the present invention, the bio-based carbon content, which is an index showing the proportion of biologically derived raw materials in the copolymerized polyethylene terephthalate resin, is preferably 5% or more, and more preferably 15% or more. The higher the bio-based carbon content, the lower the proportion of fossil resource-derived raw materials, making the container more environmentally friendly. On the other hand, as the proportion of the bio-based carbon content increases, the cost also increases, so it is more preferable that it is within an appropriate range. The bio-based carbon content can be indicated by the value of the C14 content obtained by a radiocarbon (C14) measurement method in accordance with ISO-16620-2 (equivalent to the ASTM-D6866 standard). That is, since fossil resources contain almost no C14, while biological resources contain a certain proportion of C14 (105.5 pMC), if the content of C14 in the copolymerized polyethylene terephthalate resin is PC14, the bio-based carbon content can be calculated by the following formula.
[0042] Bio-based carbon content (%) = PC14 / 105.5 x 100 Next, FIG. 3 is a cross-sectional view showing the overall structure of a container according to a second embodiment of the present invention.
[0043] Since the container 21 according to the second embodiment of the present invention has a basically similar structure to the container 1 according to the above-mentioned first embodiment, the following description will focus on the differences.
[0044] 1, the container 21 is formed by press molding a sheet of base paper obtained from a composite substrate 27 (having the same configuration as the composite substrate 7 in the first embodiment described above). Specifically, the sheet of base paper obtained from the composite substrate 27 is punched out into a predetermined shape and then press molded to form the container 21 having a bottom 22 and a side wall 23 rising from the periphery of the bottom 22.
[0045] Furthermore, although not shown, the container according to the third embodiment is formed by folding a sheet of base paper obtained from a composite substrate (having the same configuration as the composite substrate 7 in the first embodiment described above) and forming it into a predetermined container shape. Specifically, after punching out a sheet of base paper obtained from the composite substrate in a predetermined shape, the base paper is folded or the like to form a bottom and sidewalls rising from the periphery of the bottom, thereby forming a container having a bottom and sidewalls rising from the periphery of the bottom.
[0046] The containers according to the embodiments of the present invention can be used for various purposes, and the purposes are not limited thereto, but can be used, for example, for storing food. In particular, they are suitable for storing food that is heated under high temperature conditions after being filled in the container. Specifically, they can be used under high temperature heating conditions of 100°C or higher, and can be called heat-resistant paper containers. They can also be used for cooking in ovens (including toasters, grills, etc.) at 200°C or higher.
[0047] In the containers according to the embodiments of the present invention, the composition of the paper constituting the composite substrate is not particularly limited, and pure white roll paper, kraft paper, parchment paper, ivory paper, Manila paper, card paper, cup paper, etc. can be used depending on the desired application. In addition, the basis weight of the paper is 150 g / m 2 ~500g / m 2 By configuring in this manner, molding of the container becomes easy and the cost of the container can be reduced.
[0048] Furthermore, in the containers according to the embodiments of the present invention, the method of laminating the polyethylene terephthalate resin onto the paper is not particularly limited, and examples include extrusion lamination, heat lamination, dry lamination, wet lamination, etc. In the present invention, the use of extrusion lamination is preferable because it is suitable for mass production, is cost-effective, and allows direct lamination without an anchor coat, etc. However, this does not exclude the formation of an anchor coat layer on the paper beforehand during extrusion lamination.
[0049] Furthermore, in the container according to each embodiment of the present invention, the thickness of the resin layer is not particularly limited, but is preferably 6 μm to 50 μm. Within this range, the desired heat resistance can be imparted to the container. In addition, when the resin layers of the composite substrate are thermally bonded to each other in container molding, the temperature of the resin can be easily raised uniformly, making it possible to achieve uniform adhesion. Furthermore, the occurrence of tunneling or pinholes in the resin layer during thermal bonding can be suppressed.
[0050] Furthermore, in the containers according to each embodiment of the present invention, the resin layer is formed on the inner surface of the base material layer, but it is sufficient that it is formed on at least one surface, and it may also be formed on both surfaces.
[0051] Furthermore, in the container according to each embodiment of the present invention, an anchor coat layer may be interposed between the base layer and the resin layer as described above, or a printed layer may be formed, as long as the object of the present invention is not impaired. Also, the paper of the base layer may be subjected to a corona treatment.
[0052] Furthermore, in the containers according to each embodiment of the present invention, the copolymerized polyethylene terephthalate resin may contain appropriate amounts of various additives such as chain extenders, ultraviolet absorbers, lubricants, antistatic agents, heat stabilizers, antioxidants, pigments, dyes, hydrolysis inhibitors, light stabilizers, and plasticizers, within the scope that does not impair the object of the present invention.
[0053] Furthermore, in the containers according to each embodiment of the present invention, the method for producing the copolymerized polyethylene terephthalate resin obtained by copolymerization with isophthalic acid is not particularly limited, and the copolymerization may be performed by a known method and under known conditions, and multiple polyethylene terephthalate resins may be mixed to adjust the copolymerization ratio, as described above. EXAMPLES
[0054] The present invention will be described in detail below with reference to examples, although the embodiments of the present invention are not limited to the examples.
[0055] (Preparation of Examples) First, multiple types of copolymerized polyethylene terephthalate resins were prepared by copolymerizing with isophthalic acid at different ratios, or by mixing multiple polyethylene terephthalate resins with different copolymerization ratios to adjust them to a predetermined copolymerization ratio, etc. As the resin used in Examples 1 and 3, a biomass polyethylene terephthalate resin was prepared, and as the resin used in Comparative Example 1, a homopolyethylene terephthalate resin was prepared. 1 The ratio (%) of "isophthalic acid monomer unit molar ratio" to "total of terephthalic acid monomer unit molar ratio and isophthalic acid monomer unit molar ratio" was calculated by qualitative and quantitative analysis using H-NMR measurement. As a result, the copolymerization ratio of isophthalic acid in each copolymerized polyethylene terephthalate resin was 2.0% (Example 1), 1.6% (Example 2), 5.0% (Example 3), 7.5% (Example 4), 9.2% (Example 5), 14.1% (Comparative Example 2), and 10.5% (Comparative Example 3). The copolymerization ratio of isophthalic acid in the homopolyethylene terephthalate resin was 0% (Comparative Example 1). In addition, the melting points of each were measured using a commercially available differential scanning calorimeter. Furthermore, the bio-based carbon content was measured using a radiocarbon (C14) measurement method in accordance with ISO-16620-2 (equivalent to the ASTM-D6866 standard) and calculated using the above-mentioned bio-based carbon content calculation formula.
[0056] Basis weight 230g / m 2 The above paper was used as a substrate layer, and one side of the substrate was coated by extrusion lamination with each of the above-mentioned types of polyethylene terephthalate resins to a thickness of 30 μm in Examples 1, 2, 4, and Comparative Examples 1 to 3, a thickness of 40 μm in Example 3, and a thickness of 20 μm in Example 5, to prepare each composite substrate. The thickness of the polyethylene terephthalate resin was measured by observing the cross section of the composite substrate with a commercially available microscope.
[0057] Side wall members and bottom members of a predetermined shape that would create a container large enough to hold 300 g of the white sauce described below were punched out from each type of composite substrate, and these were then combined and joined by thermal bonding to produce the containers of Examples 1 to 5 and Comparative Examples 1 to 3.
[0058] (Adhesion test) Test pieces measuring 50 mm × 150 mm were cut out from each of the types of composite substrates prepared above, and a peel test was performed at 180° peeling speed of 100 mm / min to test the adhesion between the substrate layer and the resin layer of the composite substrate.
[0059] The measuring device used was a MAX-R2KN-B model manufactured by Japan Measurement Systems Co., Ltd. The ideal adhesion is complete peeling between the paper layers, but it was determined that there was no problem if there was enough strength to cause partial peeling between the paper layers. In addition, adhesion was evaluated as follows: less than 4N / 50mm was × (not suitable), 4N / 50mm to less than 7N / 50mm was △ (acceptable), and 7N / 50mm or more was ○ (suitable).
[0060] (Heat resistance test) Using each of the types of containers prepared above, the following two types of heat resistance tests were carried out.
[0061] (1) Microwave oven heating test 100g of water was put into each container, and heated in a microwave oven (manufactured by SANYO Electric Co., Ltd., model number: EMO-FM23C, without turntable) at 500W for 3 minutes, then removed, and the container was left for 12 hours with water in it, after which the presence or absence of water leakage from the container and the surface condition of the resin layer constituting the container were visually confirmed. The test was performed with n=5 containers for each container. The water leakage evaluation was judged as ◯ (good) when no water leakage occurred in any of the 5 containers, and × (not good) when water leakage occurred in even one of the 5 containers. The evaluation of the surface condition of the resin layer was judged as ◯ (good) when no abnormality such as air bubbles or tears was found on the surface of the resin layer constituting the container in any of the 5 containers, and × (not good) when abnormality such as air bubbles or tears was found on the surface of the resin layer constituting the container in even one of the 5 containers.
[0062] (2) Baking test after filling containers with white sauce Each container was filled with 300g of white sauce manufactured by Heinz Japan Co., Ltd., and then the filled container was heated in an oven manufactured by Fujimak Co., Ltd. (model number: FSCC101) at heating temperatures of 200°C and 260°C for a heating time of 5 minutes in each case to carry out a baking test. The test was carried out at each temperature with n=5. After the baking test, the white sauce was removed from the container, and the presence or absence of delamination (peeling at the interface between the paper, which is the base layer, and the resin layer) between the base layer (paper) and the resin layer of the composite base material constituting the container was visually confirmed. When no delamination occurred anywhere on the container, it was judged as ◯ (suitable), and when delamination occurred anywhere on the container, it was judged as × (unsuitable).
[0063] Table 1 below shows the composition of each type of container (resin, composite substrate) and the results of each test.
[0064] [Table 1] As shown in Table 1, in Examples 1 to 5 in which the copolymerization ratio of isophthalic acid is within the preferred range, the adhesion is preferred and the heat resistance is also satisfactory in the baking test at a heating temperature of 200° C. In particular, the heat resistance of Examples 1 to 4 in which the copolymerization ratio of isophthalic acid is 1.5 mol % or more and 8 mol % or less showed preferred results even in the baking test at a heating temperature of 260° C.
[0065] It was also confirmed that Example 1, in which the bio-based carbon content was 17%, and Example 3, in which the bio-based carbon content was 6.2%, also had favorable adhesion and heat resistance, similar to the other Examples in which the bio-based carbon content was 0%. [Industrial Applicability]
[0066] As described above, the container according to the present invention is suitable as, for example, a paper cup or case for storing beverages, food, etc.
Claims
1. A container (1) comprising a composite substrate (7) including a base layer (10) made of paper and a resin layer (11) made of copolymerized polyethylene terephthalate resin laminated on at least one surface of the base layer, The copolymerized polyethylene terephthalate resin is a copolymerized polyethylene terephthalate resin obtained by copolymerization with isophthalic acid, a copolymerization ratio of the isophthalic acid in the copolymerized polyethylene terephthalate resin is 1.5 mol % or more and 2.2 mol % or less, The copolymerized polyethylene terephthalate resin has a melting point of 235° C. or higher and 250° C. or lower, The adhesion of the resin layer to the base layer is 4 N / 50 mm or more; A container in which 100 g of water is placed in the container, heated in a microwave oven at 500 W for 3 minutes, and then removed. After the container is left with the water in it for 12 hours, there is no water leakage from the container and no abnormalities such as air bubbles or tears appear on the surface of the resin layer. The container is filled with 300 g of white sauce and then heated in an oven at a heating temperature of 200°C and 260°C for a heating time of 5 minutes in both cases, and in either case, no delamination occurs between the base material layer and the resin layer of the composite base material that constitutes the container.
2. The container according to claim 1 , wherein the copolymerized polyethylene terephthalate resin is a biomass polyethylene terephthalate resin derived from living organisms, the biomass polyethylene terephthalate resin having a bio-based carbon content of 5% or more.
3. The container has a bottom (2) and a side wall (3) rising from the periphery of the bottom, 3. The container according to claim 1, wherein the bottom and the side wall are connected by thermal bonding.
4. A container described in any one of claims 1 to 3, wherein the container is a press-molded product or a folded molded product.
5. The container according to any one of claims 1 to 4, wherein the resin layer has a thickness of 6 µm to 30 µm.
Citation Information
Patent Citations
Thinninggout filter for sampled value
JP1981080917A
Polyester resin composition, film, and method of lowering low-molecular-weight compound content of polyester
JP2001072747A
Packaging container
JP2002337840A
Paper cup and its manufacturing method
JP2004018101A
Polyester resin and binder fiber
JP2011012154A